تصور عن منهاج تدريس اللغة العربية في المرحلة الثانوية - أ. أنس بوسلام; أ. فاطمة طاهري (Prosiding Konferensi Nasional Bahasa Arab, 2021)
The research deals with a conception of the Arabic language teaching curriculum, by addressing the most important curricular elements, starting with the references for building the Arabic language curriculum and its literature, the curriculum objectives, then the targeted competencies, the principles of choosing the contents, and finally the methods of teaching Arabic through